Thyroid Hormone and the Brain: Mechanisms of Action in Development and Role in Protection and Promotion of Recovery after Brain Injury - Liu, Yan-Yun (Pharmacol Ther, 2018)
Thyroid hormone (TH) is essential for normal brain development and may also promote recovery and neuronal regeneration after brain injury. TH acts predominantly through the nuclear receptors, TH receptor alpha (THRA) and beta (THRB). Additional factors that impact TH action in the brain include metabolism, activation of thyroxine (T4) to triiodothyronine (T3) by the enzyme 5′-deiodinase Type 2 (Dio2), inactivation by the enzyme 5-deiodinase Type 3 (Dio3) to reverse T3 (rT3), which occurs in glial cells, and uptake by the Mct8 transporter in neurons. Traumatic brain injury (TBI) is associated with inflammation, metabolic alterations and neural death. In clinical studies, central hypothyroidism, due to hypothalamic and pituitary dysfunction, has been found in some individuals after brain injury. TH has been shown, in animal models, to be protective for the damage incurred from brain injury and may have a role to limit injury and promote recovery. Although clinical trials have not yet been reported, findings from in vitro and in vivo models inform potential treatment strategies utilizing TH for protection and promotion of recovery after brain injury.